Evaluation of the Rock Climbing Training Program for the Southwest Papua BAPOMI Team in Preparation for POMNAS - Mudji Mulyani; Waskito Aji Suryo Putro; Saiful Anwar (Universitas Hamzanwadi, 2026)
This study evaluated the rock climbing training program implemented by the Southwest Papua BAPOMI team in preparation for the 2025 National Student Sports Week (POMNAS). The main problem identified was the lack of comprehensive evaluation regarding the effectiveness of the training program, particularly in terms of resource adequacy and implementation quality. This research aimed to assess the program using the CIPP (Context, Input, Process, Product) evaluation model. The study employed a descriptive evaluation design involving 14 respondents consisting of athletes, coaches, team managers, and BAPOMI administrators. Data were collected through questionnaires, interviews, observations, and documentation. The findings revealed that the context component achieved 78% (Good category), indicating appropriate program planning and objectives. However, the input component scored only 46% (Poor category), highlighting significant limitations in funding, facilities, infrastructure, and organizational support. The process and product components both achieved 100% (Very Good category), demonstrating consistent program implementation and positive outcomes, including two silver medals and two bronze medals at POMNAS 2025. In conclusion, the training program was generally effective, but resource constraints remain the primary challenge requiring immediate attention. Improvements in financial support and infrastructure are essential to sustain and enhance the program's positive achievements. The CIPP model proved effective in identifying specific program strengths and weaknesses.